2018
DOI: 10.2196/cardio.9153
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intelligent Two-Way Communication System for Remote Heart Failure Medication Uptitration (the CardioCoach Study): Randomized Controlled Feasibility Trial

Abstract: BackgroundEuropean Society of Cardiology guidelines for the treatment of heart failure (HF) prescribe uptitration of angiotensin-converting enzyme inhibitors (ACE-I) and β-blockers to the maximum-tolerated, evidence-based dose. Although HF prognosis can drastically improve when correctly implementing these guidelines, studies have shown that they are insufficiently implemented in clinical practice.ObjectiveThe aim of this study was to verify whether supplementing the usual care with the CardioCoach follow-up t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Patient engagement with mHealth interventions was measured solely based on system usage data in 72% (23/32) of the studies. Among the remaining studies, 6% (2/32) used only qualitative methods to determine engagement (focus groups and semistructured interviews) [ 34 , 39 ]; 19% (6/32) [ 14 , 40 , 48 , 54 , 57 , 62 ] used both system usage data and qualitative methods; and 3% (1/32) [ 43 ] planned to use system usage data, qualitative methods (think aloud), and user engagement questionnaires.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient engagement with mHealth interventions was measured solely based on system usage data in 72% (23/32) of the studies. Among the remaining studies, 6% (2/32) used only qualitative methods to determine engagement (focus groups and semistructured interviews) [ 34 , 39 ]; 19% (6/32) [ 14 , 40 , 48 , 54 , 57 , 62 ] used both system usage data and qualitative methods; and 3% (1/32) [ 43 ] planned to use system usage data, qualitative methods (think aloud), and user engagement questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…In 20% (6/30) of the 30 studies [ 35 , 44 , 52 , 54 , 55 , 58 ], system usage data were operationalized as the number of assigned tasks completed per patient per number of days equipped with a mobile device or intervention. In 1 of the 6 studies [ 35 ], investigators reported a mean engagement of 5.7%, with a range of 0 to 27, while in the remaining studies, engagement was reported as an overall rate, ranging from 53.3% to 95%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the uptake and titration of guideline-recommended medical HF therapy could be improved further [ 7 , 8 , 9 , 10 ]. Remote monitoring strategies can be used to aid clinicians in the up-titration of guideline-recommended medical HF therapy [ 11 ]. Over the last years, multiple monitoring strategies, such as non-invasive remote monitoring (consisting of structured telephone support or non-invasively monitoring of parameters including body weight, blood pressure, and heart rate), monitoring using cardiac implantable electronic devices (such as implantable cardioverter-defibrillator or cardiac resynchronization therapy devices) and invasive remote hemodynamic monitoring, have been proposed and tested [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%